Greenhouse gas (GHG) emissions in the Sultanate of Oman. Issue 3 (20th April 2015) - Abdul‐Wahab, Sabah Ahmed; Charabi, Yassine; Al‐Rawas, Ghazi A.; Al‐Maamari, Rashid; Gastli, Adel; Chan, Keziah
Abstract Worldwide, many countries are being affected by greenhouse gas (GHG) emissions. The Sultanate of Oman is no exception. In Oman, both oil‐ and natural‐gas‐related activities have the most important shares of the nation's Gross Domestic Product (GDP). Hence, they are expected to be the primary cause of GHG emissions within the country. In this study, the greenhouse carbon dioxide emissions (CO2) released from the fossil fuels (i.e., oil and natural gas) used in the country for energy production purposes was computed by using the Intergovernmental Panel on Climate Change (IPCC) reference approach for National Greenhouse Gas Inventories. The objective was to develop the CO2 emissions for Oman over the last 40 years starting from year 1972. The obtained results indicated that Oman has a growth in its CO2 GHG emissions. This study is very important and essential, as it will assist Oman to monitor its progress in reducing CO2 emissions. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd